Incretin responses to oral glucose load in Japanese non-obese healthy subjects - Nagai, Etsuko (Springer Healthcare Communications, 2011)
INTRODUCTION: Recently, incretin-related therapy has been developed for the new treatment of diabetes mellitus; however, incretin response to glucose ingestion in normal glucose tolerant (NGT) subjects has not been clarified in detail with special reference to the role of incretin hormones, glucagon, and a family history of diabetes. METHODS: We conducted a 75 g oral glucose tolerance test in 30 NGT subjects. RESULTS: The total glucose-dependent insulinotropic peptide (GIP)-AUC(0–120) (area under the curve over a period of 0–120 minutes) was correlated with immunoreactive insulin (IRI)-AUC(0–120) (P<0.05), insulinogenic index (II; P<0.05), ΔIRI between 0 and 120 minutes (P<0.05). Active glucagon-like peptide-1 (GLP-1) AUC(0–120) was correlated inversely both with Δ glucose between 0 and 30 minutes (P<0.01) and with Δ immunoreactive glucagon between 0 and 30 minutes (P<0.05). Δ Total GIP between 0 and 15 minutes (P<0.01), Δ total GIP between 0 and 30 minutes (P<0.05), and the total GIP-AUC(0–120) (P<0.05) in the subjects with a family history of type 2 diabetes were significantly higher than those in the subjects without a family history. CONCLUSION: These results suggest that GIP possibly facilitates insulin secretion in response to oral glucose load directly and active GLP-1 may exert the glucoregulatory action via the suppression of glucagon secretion in NGT subjects. Notably, the subjects with a family history of diabetes exert significantly higher GIP response in the early phase of glucose load compared with those without a family history.